“Correspondemos a uma aspiração de nossa classe”: o pós-abolição a partir do jornal O Astro (Cachoeira e Rio Pardo, RS) - Sônego, Aline (2022)
The present study is linked to the Postgraduate Program in History/UFSM, area of concentration: History, Power and Culture, and the Research Line: Culture, Migrations and Work and proposes to relate the study on the black press to the new perspectives on postabolition in Brazil. In this sense, this thesis is dedicated to studying O Astro, a periodical that circulated in the municipalities of Cachoeira and Rio Pardo in the southern Rio Grande do Sul in 1927 and 1928. Founded by public servants José de Farias and Manoel Etelcides da Silva, it was a “social organ of the color element of this city”. Considering this form as a possibility of being a spokesperson for that community, we seek to understand what were the concerns, desires, and themes expressed there and how they guided the construction of citizenship in that post-abolition period. The periodical will be analyzed as the starting point for investigating a larger context, in which black experiences are immersed in a deeply racialized society, which brought impediments on several fronts, whether in the invisibility built from the printed records of the city, in racism which descended from public spaces and social places, as well as in its most tragic consequences, such as the murder of a black man from Rio Pardo who fought for the right to land. In the writings of O Astro, it is understood that the struggles and resistances of black people took place daily, whether in the valuation and racial positivism, in the reflections on the construction of citizenship, in the highlight of black public personalities, in the tributes to individualities, as well as in publicizing and supporting the various social, recreational, religious and sports organizations in the black communities of Cachoeira and Rio Pardo. In this sense, it is argued that O Astro, as a representative of the black press that was articulated in the region, confers the materiality of a relational dimension that has much deeper origins as a social group, thus adding to the historiographical studies that have been demonstrating black protagonism in the post-abolition period. Therefore, in addition to researching and understanding the founders‟ trajectory, we seek to know the “receivers”, that is, the reading community involved and how their lives were intertwined with the ideals of O Astro. For this, together with the historiographical debate on the black press and the post-abolition period in Brazil, it was also based on the theoreticalmethodological foundations of micro-history to assist in the crossing of sources to reconstitute the social experiences of the people who were part of the black communities of Cachoeira and Rio Pardo. The black press will not be analyzed only as an individual endeavor of the founders understood as black intellectuals, but how it articulated itself with the various strategies in the post-abolition period, as a social group.